(untitled) (Research, Society and Development, 2016)
The residue of cooking oil originating from the residences, commerce and industry is a potentially polluting material when improperly discarded, requiring alternatives that enable its recycling, by stimulating the balance between the environmental, economic and social contexts. Companies increasingly are taken to engage with the reverse logistics of their products, and this establishes a precedent for the technology market and its benefits in the generation of knowledge through raw data mining, providing visibility to those who invest in it. Taking as object of study the issues around pollution by saturated cooking oil, this study will present the projection of a Management Information System platform that displays information of the pollution potential of the cooking oil as a way of competitive advantage for companies in the field that practice reverse logistics. This article shows a case study of a system development and tested in companies that practice reverse logistics. The results are encouraging with the system being useful to end users, which provides validation.